2017
DOI: 10.3390/cryst7050134
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of AlN Insertion Layer in Stress Control of GaN on 150-mm Si (111) Substrate

Abstract: Abstract:In this study, low-temperature (LT) and high-temperature (HT) AlN insertion layers (ILs) grown at 680 and 970 • C were integrated with 3.7-µm GaN-based heterostructure grown on 150-mm Si (111) substrates by metalorganic chemical vapor deposition. Under a V/III flow ratio of 1960, the GaN epilayer with a continuous interface resulting from the LT AlN IL was subject to a compressive stress of −0.109 GPa. However, the GaN epilayer with discontinuous interfaces resulting from the HT AlN IL growth under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…4b), AlN/GaN superlattice, 23 or multiple AlN stress release insertion layers. 24 High-performance GaN epitaxial layers have been successfully grown on 6-inch (c.150 mm) and 8-inch (c.200 mm) (111) Si wafers. 20 Despite the aforementioned challenges, GaN-on-Si power transistors are still an attractive option to compete with other GaN transistors on different substrates, thanks to their cost-effectiveness and simple fabrication steps for mass production.…”
Section: Gan-on-si Substratementioning
confidence: 99%
See 1 more Smart Citation
“…4b), AlN/GaN superlattice, 23 or multiple AlN stress release insertion layers. 24 High-performance GaN epitaxial layers have been successfully grown on 6-inch (c.150 mm) and 8-inch (c.200 mm) (111) Si wafers. 20 Despite the aforementioned challenges, GaN-on-Si power transistors are still an attractive option to compete with other GaN transistors on different substrates, thanks to their cost-effectiveness and simple fabrication steps for mass production.…”
Section: Gan-on-si Substratementioning
confidence: 99%
“…Flip-chip assembly has been introduced to provide direct electrical connections without bonding wires. 24,43,101 Many researchers have reported that the contact between a metal wire and a pad surface is one of the weakest points which tends to cause mechanical failures before the transistor malfunctions. [102][103][104] Therefore, modules assembled with the flip-chip bonding are preferred due to the absence of wire-to-pad contacts.…”
Section: Packagingmentioning
confidence: 99%
“…In the first paper, Y. Kawakami's group studied the interface formation of AlN on sapphire substrate by EVPE, which is a new AlN bulk fabrication method using Al and N 2 as precursors, for AlN bulk crystals that are promising substrates for AlGaN-based deep ultraviolet light emitters and high-frequency electronic devices with high-breakdown voltages [15]. For the second paper, Wuu's group investigated the role of AlN insertion layer in stress control of GaN on Si(111) substrate by metalorganic chemical vapor deposition (MOCVD) for high-frequency and high-power electronic devices [16]. Horng's group studied the effects of a corona-discharge plasma treatment on the performance of an AlGaN/GaN metal-oxide-semiconductor high-electron mobility transistor fabricated on Si substrates [17].…”
Section: Current Perspectives In the Applications Of Nanostructured Ganmentioning
confidence: 99%
“…Comparatively, high-temperature (HT)-AlN layers yield reduced dislocation densities and promote the relaxation of compressive strain due to an increased Al migration length. In addition, many studies are also investigated the high-quality GaN layer grown on a Si substrate using the HT- and LT-AlN growth process [ 17 , 18 ]. Moreover, Hirayama et al used an AlN buffer layer grown with pulsed NH 3 flow on a sapphire substrate [ 19 ], which is an effective way to enhance the lateral migration of Al atoms and produce a smooth epitaxial surface.…”
Section: Introductionmentioning
confidence: 99%